Blind recognition of STBC based on higher-order cumulants - Li-min ZHANG; Qing LING; Wen-jun YAN (Tongxin xuebao)
Aiming at the problems for blind recognition of space-time block code(STBC)in MIMO communication sys-tems,a method was exploited based on higher-order cumulants of received signals.Firstly,the model of received signals was given and the fourth-order cumulants of the received signals in multiple input single output(MISO)systems was ob-tained.Secondly,using the characteristics of coding matrix,it was proved that the fourth-order cumulants in different de-lay vectors presented non-null value that depended on the STBC sat the transmitter side.Finally,a classifier for the STBC was presented based on the Euclid distance between the experimental values of fourth-order cumulants and the theoretical ones.Simulations show that the method performs well even for low signal to noise ratio.